2021
DOI: 10.5194/acp-21-6985-2021
|View full text |Cite
|
Sign up to set email alerts
|

Robust winter warming over Eurasia under stratospheric sulfate geoengineering – the role of stratospheric dynamics

Abstract: Abstract. It has been suggested that increased stratospheric sulfate aerosol loadings following large, low latitude volcanic eruptions can lead to wintertime warming over Eurasia through dynamical stratosphere–troposphere coupling. We here investigate the proposed connection in the context of hypothetical future stratospheric sulfate geoengineering in the Geoengineering Large Ensemble simulations. In those geoengineering simulations, we find that stratospheric circulation anomalies that resemble the positive p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 56 publications
8
48
0
Order By: Relevance
“…The issue of wintertime precipitation changes driven by changes in the phase of the NAO and the associated changes in the strength and position of the North Atlantic storm-track are unlikely to be solved by injecting SO2 using more sophisticated geographic injection strategies owing to the relatively long lifetime of the sulphate aerosols in the stratosphere during which they may be transported (and induce stratospheric heating) far from the injection site. Simpson et al (2018) and Banerjee et al (2021) both performed simulations using the Geoengineering Large Ensemble (Tilmes et al, 2018b) where the injections were performed at latitudes of 30° N, 15° N, 15° S and 30° S and both studies found a very similar forced positive phase of the DJF NAO to that found here in G6sulfur using equatorial injection. Simpson et al (2018) performed further experiments where the stratospheric heating was enhanced and found a stronger impact on the positive phase of the DJF NAO and the associated precipitation patterns, suggesting that the absorption of solar radiation at wavelengths greater than ~1.3 µm by stratospheric sulphate (Dykema et al, 2016) is the root cause of this response.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The issue of wintertime precipitation changes driven by changes in the phase of the NAO and the associated changes in the strength and position of the North Atlantic storm-track are unlikely to be solved by injecting SO2 using more sophisticated geographic injection strategies owing to the relatively long lifetime of the sulphate aerosols in the stratosphere during which they may be transported (and induce stratospheric heating) far from the injection site. Simpson et al (2018) and Banerjee et al (2021) both performed simulations using the Geoengineering Large Ensemble (Tilmes et al, 2018b) where the injections were performed at latitudes of 30° N, 15° N, 15° S and 30° S and both studies found a very similar forced positive phase of the DJF NAO to that found here in G6sulfur using equatorial injection. Simpson et al (2018) performed further experiments where the stratospheric heating was enhanced and found a stronger impact on the positive phase of the DJF NAO and the associated precipitation patterns, suggesting that the absorption of solar radiation at wavelengths greater than ~1.3 µm by stratospheric sulphate (Dykema et al, 2016) is the root cause of this response.…”
Section: Discussionmentioning
confidence: 52%
“…While varying in degree, all models show a clear warming over northern Eurasia consistent with the positive NAO anomaly (Hurrell, 1995;Shindell et al, 2004), although the warming is still less than in ssp585. They also show cooling over the Labrador Sea and warming over the eastern USA, again as expected from a long term positive shift in the NAO (Scaife et al, 2005), although the picture is less consistent for differences over North America (Banerjee et al, 2021;Jones et al, 2021). The corresponding differences in Northern Hemisphere wintertime precipitation are shown in Fig.…”
Section: Impact On the Naomentioning
confidence: 59%
See 1 more Smart Citation
“…At this point then, one is inevitably led to ask: if Pinatubo and Krakatau are not large enough, how large does an eruption need to be to cause wintertime surface warming at Northern mid-latitudes? At the upper bound, in a geoengineering context, it has recently been shown that large and sustained stratospheric sulfate injections do indeed produce wintertime warming over Eurasia (Kravitz et al, 2017, see their Figure 8, bottom right panel), and this surface warming (which is absent in the summer months) has been linked to stratosphere-troposphere dynamical coupling affecting the NAO (Banerjee et al, 2020). DallaSanta et al (2019) also found a robust impact of sustained lower stratospheric tropical warming on the NAO, using an idealized model.…”
Section: Introductionmentioning
confidence: 95%
“…As mentioned before, the presence of aerosols in the stratosphere also produces a perturbation of stratospheric dynamics (Richter et al, 2017;Visioni et al, 2020a) that, in turn, might affect precipitation (Simpson et al, 2019) and temperature (Jiang et al, 2019) at the surface. The response is driven by the absorption of infrared radiation by the aerosols resulting in the heating of the stratospheric air and is thus dependent on the overall burden and the size of the particles (Pitari et al, 2016) but also on interactions with the chemical cycles in the stratosphere (Visioni et al, 2017b;Richter et al, 2017) and the incursion of water vapor from the troposphere due to the warming of the tropopause layer (Visioni et al, 2017b;Tilmes et al, 2018b;Boucher et al, 2017). In Fig.…”
Section: Differences In the Stratospheric Responsementioning
confidence: 99%